Blastocystis spp. contaminated water sources in aboriginal settlements - Noradilah, SA; Lee, IL; Anuar, TS; Salleh, FM; Manap, ASNA; Husnie, NS; Azrul, SM; Moktar, N (Malaysian Soc Parasitology Tropical Medicine, 2024)
Blastocystis has been increasingly reported in water bodies. However, lack of studies to determine the presence of Blastocystis in water used by the aborigines in Malaysia has led to the birth of this research. This study was therefore aimed to determine the occurrence of Blastocystis in water samples in aboriginal settlements in Pahang, Malaysia. Water samples collected from seven sampling points of two rivers and other water sources in the villages were subjected to filtration and cultivation followed by trichrome staining. The trichrome stained slides were observed microscopically under 1000X magnification for the presence of Blastocystis. River samples were also measured for physicochemical parameters. From this study, 42.9% of the river water and 6.25% of other water samples were positive for Blastocystis. All river samples showed presence of Escherichia coli and Enterobacter aerogenes, indicating faecal contamination. Statistical analysis showed Blastocystis occurrence in the river were significantly correlated conductivity, turbidity, chemical oxygen demand (COD), total dissolved solid (TDS), concentration of sulfate and faecal coliforms. The river water used by the aborigines is a probable source for Blastocystis transmission in this community. Therefore, protection of the river from organic material and faecal contaminations are highly required in order to control the contamination by Blastocystis.